Konsep Pemberdayaan Masyarakat versus Pengembangan Masyarakat: Studi Komparatif dalam Konteks Pembangunan Sosial di Indonesia - Rasyid, Abd.; Pulubuhu, Dwia Aries Tina; Muhammad, Rahmat (CV. Social Politic Genius (SIGn), 2024)
Community interventions through community empowerment and community advancement are crucial within Indonesia’s social development agenda, yet their effectiveness is often constrained by conceptual ambiguity between these two approaches. This research aimed to conduct an in-depth comparative study of community empowerment versus community advancement within the Indonesian context, encompassing a comparative analysis of concepts and theoretical foundations, a review of program implementation examples, and identifying their application challenges and opportunities. Employing a qualitative approach with a literature study method and secondary document analysis, this study thematically and comparatively analyzed various textual data sources. The analysis revealed fundamental differences between the two concepts: community empowerment inherently focuses on enhancing agency and shifting power relations, while community advancement is more oriented towards improving socio-economic conditions and infrastructure, although conceptual intersections and significant terminological conflation were also identified. In terms of implementation, programs reflecting community empowerment tend to emphasize substantive participation and strengthening internal capacities, whereas advancement-oriented programs focus more on achieving physical outputs; however, hybrid practices and the strong influence of contextual variations are prominent in the field. Both approaches face systemic challenges (e.g., institutional capacity, sustainability) and specific challenges (e.g., elite capture in empowerment, maintenance issues in advancement), yet opportunities for synergy also exist through decentralization frameworks and technology adoption. It is concluded that a clear understanding of the essential differences, similarities, and potential synergies between community empowerment and community advancement forms a fundamental basis for designing and implementing more effective, contextual, adaptive, and transformative social development interventions in Indonesia.